The Significance of the Propositional Truths in Christian Faith - Muriwali Yanto Matalu (Verbum Christi: Jurnal Teologi Reformed Injili, 2016)
Postmodernism philosophy has made a serious impact to some Christian thinkers on how they view the truth. During many decades ago, Christian theologians had formulated and defended the Christian theology as a system of propositional truths. However, in some recent decades the truth - as propositions which are expected to become timeless truths -has been declined by some thinkers like Leslie Newbigin and Stanley Grenz. One of the primary reasons to reject propositions in theological discourse, according to them, that it is a product of the enlightenment and therefore cannot be applied in the postmodern context. Yet, this view has a significant problem and therefore the aim of this article is to elaborate the problem and to maintain the significance of the propositional truths in Christian faith.